Desenvolvimento e caracterização físco-química de geleias de camu-camu (Myciaria dubia), maracujá-do-mato (Passiflora nitida) e cacau (Theobroma cacao) - Silva, Vanda Peres da (Brasil, 2023)
The native fruits of the Amazon region have great potential to boost the national economy. However, there is a lack of studies on the composition of these fruits, which makes it difficult to develop innovative and quality products with this raw material. The objective of this work was to develop and characterize jams based on camu-camu (Myrciaria dubia), wild passion fruit (Passiflora nitida) and cocoa (Theobroma cocoa). The fruits were purchased at the municipal fair of Coari-AM. The physical-chemical analyzes of pulps and jellies were carried out in triplicate and on a wet basis. The camu-camu pulp had pH 3.39, acidity 5.12 g/100g, moisture 95.10 g/100g, ash 0.21 g/100g, protein 0.57 g/100g, lipids 0.23 g/ 100g and total carbohydrate 4.10 g/100g. The wild passion fruit pulp obtained values of pH 3.39 g/100g, acidity 4.52 g/100g, moisture 85.41 g/100g, ash 0.67 g/100g, protein 1.05 g/100g , lipids 0.63 g/100g and carbohydrate 12.67 g/100g. The pH of the cocoa pulp was 3.56, acidity 2.32 g/100g, moisture 72.10 g/100g, ash 0.11 g/100g, protein 2.86 g/100g, lipids 1.28 g /100g, carbs 22.64g/100g. The pH of the camu-camu jelly was 3.38, acidity 72.24 g/100g, ash 0.21 g/100g, protein 0.72 g/100g, lipids 0.17 g/100g and carbohydrate 65.80 g /100g. The pH of wild passion fruit jelly was 3.90, acidity 3.72 g/100g, moisture 44.41 g/100g, ash 4.68 g/100g, proteins 1.79 g/100g, lipids 0, 90 g/100g and carbohydrates 48.20 g/100g. For cocoa jelly, the pH found was 3.96, acidity 1.67 g/100g, moisture 46.96 g/100g, ash 0.48 g/100g, protein 1.09 g/100g, lipids 0.80 g /100g and carbohydrates 50.65 g/100g. All formulated fruits and jellies had pectin, a natural soluble fiber of these fruits and which makes the addition of commercial thickeners unnecessary. In addition, the jellies developed have flavors characteristic of foods that are part of the eating habits of the Amazonian population, which may facilitate the acceptance of these products in this region.